2003
DOI: 10.1101/gr.644503
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence and Transcriptional Profile of the Boundary Between Pericentromeric Satellites and Genes on Human Chromosome Arm 10p

Abstract: Contiguous finished sequence from highly duplicated pericentromeric regions of human chromosomes is needed if we are to understand the role of pericentromeric instability in disease, and in gene and karyotype evolution. Here, we have constructed a BAC contig spanning the transition from pericentromeric satellites to genes on the short arm of human chromosome 10, and used this to generate 1.4 Mb of finished genomic sequence. Combining RT-PCR, in silico gene prediction, and paralogy analysis, we can identify two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 73 publications
8
51
1
Order By: Relevance
“…Higher-order ␣-satellite within an array is extremely homogeneous, and few other sequences have been found embedded within higher-order ␣ arrays (Schueler et al 2001;Ross et al 2005). In contrast, monomeric ␣-satellite is more heterogeneous in sequence and is extensively interspersed with non-␣-satellite sequences (Schueler et al 2001;Guy et al 2003;Kazakov et al 2003;.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Higher-order ␣-satellite within an array is extremely homogeneous, and few other sequences have been found embedded within higher-order ␣ arrays (Schueler et al 2001;Ross et al 2005). In contrast, monomeric ␣-satellite is more heterogeneous in sequence and is extensively interspersed with non-␣-satellite sequences (Schueler et al 2001;Guy et al 2003;Kazakov et al 2003;.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, monomeric ␣-satellite lacks detectable higher-order periodicity, and its constituent monomers are far less homogeneous than are higher-order repeat units . All normal human centromeres contain large arrays of higher-order ␣-satellite (Warburton and Willard 1996;Alexandrov et al 2001), and, where investigated, these arrays have been found to be bordered by more heterogeneous monomeric ␣-satellite (Wevrick et al 1992;Horvath et al 2000;Schueler et al 2001;Guy et al 2003;. The adjacent organization of higherorder and monomeric ␣-satellite, as well as the fact that lower primates have only monomeric ␣-satellite at their centromeres (Rosenberg et al 1978;Musich et al 1980;Maio et al 1981;Thayer et al 1981;Alves et al 1994), has led to the hypothesis that higher-order ␣-satellite evolved from ancestral arrays of monomeric ␣-satellite and subsequently transposed to the centromeric regions of all great ape chromosomes (Warburton and Willard 1996;Alexandrov et al 2001;Schueler et al 2001Schueler et al , 2005Kazakov et al 2003).…”
mentioning
confidence: 99%
“…Current models of primate pericentromere evolution suggest that the complex intra-and interchromosomal duplications begin with initial euchromatin-derived seeding events, followed by exchange of large duplicated blocks to pericentromeres of nonhomologous chromosomes (She et al 2004;Horvath et al 2005). Although the Brassicaceae duplications do not appear as prevalent as those in primates, in both cases, such events could lead to the evolution of new genes (Guy et al 2003). Indeed, in O. pumila we found a novel hypothetical protein with domains likely derived from three distinct origins (Table 3).…”
Section: Pericentromeres Are Unexpectedly Gene Richmentioning
confidence: 99%
“…Several HSA7 clades contain loci mapping to both chromosome arms (Figs. 2, 3), indicating that subgroup expansion was followed by a series of duplications or inversions around the centromere, as occurred on HSA10 (Tunnacliffe et al 1993;Guy et al 2003). The pericentromeric HSA19 cluster contains a large number of ␤-satellite repeats, and unequal crossing-over between blocks of these repeats has been suggested as a factor in expansion of the cluster (Eichler et al 1998).…”
Section: Timing and Patterns Of Duplication Eventsmentioning
confidence: 99%